2000
DOI: 10.1093/jn/130.7.1809
|View full text |Cite
|
Sign up to set email alerts
|

Dietary L-Carnitine Improves Nitrogen Utilization in Growing Pigs Fed Low Energy, Fat-Containing Diets

Abstract: Growing pigs (n = 25; 17.8 +/- 0.1 kg) were used to study the effects of L-carnitine and protein intake on nitrogen (N) balance and body composition. Fat-supplemented (40 g soy oil/kg diet), corn-soybean meal basal diets containing low or high protein (136 or 180 g/diet) were formulated so that protein accretion would be limited by metabolizable energy (ME). Each basal diet was supplemented with 0 or 500 mg/kg L-carnitine and fed to pigs for 10 d in a nutrient balance trial. Final body composition was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
4
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 18 publications
4
57
4
2
Order By: Relevance
“…It could be that increased concentrations of carnitine in plasma and tissues of piglets improves the utilization of nutrients. A recent study in pigs with 20 kg body weight showed that dietary L-carnitine improves the nitrogen retention (Heo et al, 2000). Further studies, however, are needed to ascertain whether such suggestions come true.…”
Section: Discussionmentioning
confidence: 98%
“…It could be that increased concentrations of carnitine in plasma and tissues of piglets improves the utilization of nutrients. A recent study in pigs with 20 kg body weight showed that dietary L-carnitine improves the nitrogen retention (Heo et al, 2000). Further studies, however, are needed to ascertain whether such suggestions come true.…”
Section: Discussionmentioning
confidence: 98%
“…In piglets and growing pigs, L-carnitine supplementation led to a reduction in body fat and an increase in body protein (Heo et al 2000, Owen et al 2001a, 2001b. This effect is due to an enhanced rate of β-oxidation of long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…De novo synthesis is inadequate in human neonates, resulting in low plasma carnitine concentrations in premature infants [10]. Therefore, dietary carnitine supplementation is advocated for infants and, similarly, may be beneficial for domestic livestock species [11][12][13]. Studies examining systemic carnitine distribution have shown that concentrations vary widely depending on age [14], tissue [15], physiological status [16], species [17] and dietary carnitine content [18].…”
Section: Introductionmentioning
confidence: 99%